Komposisi Spesies Ekhinodermata di Perairan Tanjung Pai Padaido, Biak Numfor–Papua - Eddy Yusron; Susetiono Susetiono (Universitas Gadjah Mada, 2006)
Total of 31 species of echinoderms, consisted of 10 species holothuroidea, 9 species of asteroidea, 6 species echinoidea and 6 species ophiuroidea have been found in the Tanjung Pai, Padaido-Biak Numfor. The sea cucumbers were relatively common in the sea grass-zone. Based on population density, the sea cucumber was the dominant group and their density was the highest, but their distributions were very scarce. Among the echinoderms found in this study, only sea cucumbers were exposed to the exploitation, since its local market price was still high. Further, the diversity and density of species found at Tanjung Pai were poorer compared to the other place in Indonesian waters, such as Derawan Islands of East Kalimantan